2010
DOI: 10.1111/j.1369-7625.2010.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring public perspectives on e-health: findings from two citizen juries

Abstract: Background Interest and investment in e-health continue to grow world-wide, but there remains relatively little engagement with the public on this subject, despite calls for more public involvement in health-care planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 19 publications
3
32
0
1
Order By: Relevance
“…The U.K. Government has recently prioritised flexible access by promising that email, Skype and telephone consultations will be used to supplement face-to-face appointments with general practitioners (GPs) 3. Investigations into alternative methods of contact between doctors and patients have been conducted4 , 5 with a focus on the use of information technologies. These have described perceived low patient demand by health-care professionals and concerns about the reliability, security and confidentiality of these technologies 58.…”
Section: Introductionmentioning
confidence: 99%
“…The U.K. Government has recently prioritised flexible access by promising that email, Skype and telephone consultations will be used to supplement face-to-face appointments with general practitioners (GPs) 3. Investigations into alternative methods of contact between doctors and patients have been conducted4 , 5 with a focus on the use of information technologies. These have described perceived low patient demand by health-care professionals and concerns about the reliability, security and confidentiality of these technologies 58.…”
Section: Introductionmentioning
confidence: 99%
“…The FGD also emphasized the role of the public in maintaining communication with health facilities and providing feedback to improve the quality of health services; this was also was in accordance to what was found in England by South [11], Campbell [4] and Davis et al [12]. The FGD emphasized the need to attract and recruit highly qualified health-care professionals who are one of the main pillars of quality health-care services [5,13,14]. All groups stressed the importance of utilizing a health information technology system to improve recordkeeping and management of patient files, which would reduce costs and improve the efficiency of health services.…”
Section: Discussionmentioning
confidence: 55%
“…We believe that the process of selection of these key role players is of utmost importance and that a comfortable atmosphere is crucial for encouraging these key players to participate productively [4,[17][18][19][20]. Additionally, this is not the only method that should be employed in involving key role players in this process: it is believed that the formation of committees composed of key role players coming from different backgrounds would also be an invaluable tool in these endeavours [5,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom (UK), citizen juries contributed to explore the barriers and facilitators to the implementation of e-health services [22]. This study showed that citizens expressed a desire to be included in the development of e-health and that their suggestions were taken into account by decision-makers.…”
Section: Public Participation In the Health Sector And In Telehealthmentioning
confidence: 99%
“…In the same vein, telehealth also raises issues related to digital democracy and the right of all citizens to equally benefit from advances made in digital health, which leads several authors to call for a better consideration of the perspectives of people and communities who are, or could be, affected by these issues [12,[15][16][17][18][19]. In order to overcome such issues, at least in part, the idea of involving citizens-patients (the term refers to patients or their representatives, their family, as well as citizens, public and communities who are actual or potential users of health services) in the decisions concerning the development of telehealth services has been proposed [19][20][21][22]. Moreover, this involvement should not only occur in the evaluation of telehealth as a "technical object" (e.g.…”
Section: Introductionmentioning
confidence: 99%